2021
DOI: 10.1086/711128
|View full text |Cite
|
Sign up to set email alerts
|

Marriage Equality Laws and Youth Mental Health

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies have examined the impact of legalizing same‐sex partnerships on labour supply (Dillender, 2015), health (Dee, 2008), and health insurance (Buchmueller and Carpenter, 2012). There is a limited number of studies that examine the impact of SSMLs on employment (Sansone, 2019), health (Francis et al, 2012), suicidal ideation (Anderson, Matsuzawa and Sabia, 2021; Raifman et al, 2017), marriage (Carpenter et al, 2021), health coverage (Carpenter et al, 2021; Dillender, 2015), and mortgage credit (Miller and Park, 2018), and there are no such studies for the case of Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the impact of legalizing same‐sex partnerships on labour supply (Dillender, 2015), health (Dee, 2008), and health insurance (Buchmueller and Carpenter, 2012). There is a limited number of studies that examine the impact of SSMLs on employment (Sansone, 2019), health (Francis et al, 2012), suicidal ideation (Anderson, Matsuzawa and Sabia, 2021; Raifman et al, 2017), marriage (Carpenter et al, 2021), health coverage (Carpenter et al, 2021; Dillender, 2015), and mortgage credit (Miller and Park, 2018), and there are no such studies for the case of Europe.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the focus has shifted to considering various aspects of same-sex partnership or marriage. The impacts on different-sex marriage rates and fertility have been examined (Dillender, 2014;Trandifir, 2015), as have those on employment (Burn, 2018;Delhommer, 2020;Sansone, 2019); partners' labor supply and household bargaining (Hansen, Martell, & Roncolato, 2020;Oreffice, 2011), including effects of taxation (Isaac, 2018); and even on mental health (Anderson et al, 2021) and sexually transmitted diseases (Francis, Mialon, & Peng, 2012). 1 All of these considerations are important in understanding the position of this minority group in American society and generally.…”
Section: Introduction and The Problemmentioning
confidence: 99%
“…This result was most concentrated among LGBT adolescents. A second study found no evidence that legalizing marriage for same-sex couples decreased the probability of suicide planning and suicidal ideation among LGBT youth (Anderson, Matsuzawa, and Sabia, 2021). Taken together, these studies suggest that the mechanisms behind the potential association between marriage for same-sex couples and youth suicidal ideation remain an open question.…”
Section: Results From Repeated Surveysmentioning
confidence: 90%